How does–and how could–Te Tiriti o Waitangi inform the perceptions and praxis of the trans-Tasman alliance? - Greener BK (Informa UK Limited, trading as Taylor & Francis Group, 2024)
Te Tiriti o Waitangi is one of the founding documents of Aotearoa New Zealand. It provides for the potential for partnership between Maori and the Crown, though its promise has not been fully realised. When it comes to the trans-Tasman relationship, Te Tiriti emphasises the importance of genuine partnership, of understanding history and the depth of relationships, but it could also have further effects on the alliance with either an increased inclusion of Māori values into New Zealand’s foreign policy or increased autonomy for Māori within a domestic setting.
Keywords: New Zealand; Australia; Te Tiriti; Partnership; Identity